PERBAIKAN KUALITAS PEMBELAJARAN KEWIRAUSAHAAN DENGAN MENERAPKAN STRATEGI OPTIMALISASI KEPEMIMPINAN GURU MELALUI LEARNING MANAGER PADA SISWA KELAS X TATA BUSANA 2 DI SMK NEGERI 3 PATI - Haryati, Sri Puji (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2015)
This study aims to determine to describe: (1) implement measures tooptimize learning strategies teacher leadership through learningmanager as efforts to improve the quality of teachingEntrepreneurship in students of Class X Fashion 2 di SMK Negeri3 Pati, and (2) efforts to improve the quality of learningEntrepreneurship by applying learning strategies that optimize teacher leadershipthrough learning manager in the learning process.Classroom Action Research used model Kemmis and McTaggart. Implementationactions include four strands: (1) action planning; (2) the implementation of theaction; (3) observation; and (4) reflection. In action research with populationsstudents of Class X Fashion 2 in SMK Negeri 3 Pati amount 33 students, all ofwhich became the subject of research. Data collection techniques usedobservation, interviews, documentation and diaries, then the results wereanalyzed by calculating the percentage of: the quality of the learning process,assessment, and teacher performance.The results showed that the quality of the learning process of each Enterpriseincreased cycle, this is seen in the first cycle the average level of quality learningat 79 (degree of success